Analisis Faktor Faktor Yang Mempengaruhi Indeks Harga Saham Gabungan Di Bursa Efek Indonesia - Pradhypta, Ignatius Christian; Iskandar, Deni; Tarumingkeng, Rudy C. (Manajemen Bisnis Kompetensi, 2018)
Capital market conditions, a country heavily influenced by various factors namely internal and external macro-economic state that the influence of other countries. This study aims to identify and analyze the influence of the Hang Seng Index, Rupiah exchange rate to the US dollar, inflation, and interest rates BI on Stock Price Index (CSPI) in the period 2010- 2015, either partially or simultaneously. Data used in the form of secondary data obtained through related websites. Data analysis method used is multiple linear regression analysis with significance level of 0.05. The conclusion of this study is during the period of 2010- 2015, the partial Hang Seng Index, Rupiah exchange rate against the US dollar, and the inflation rate significantly affect JCI. While the BI rate has no effect on JCI. In addition it was found that the value of R-square is 59.3%. This means that 59.3% JCI movement can be predicted through the four independent variables.Keywords: JCI, macro-economics, Hang Seng Index